Analisis Pendapatan Penangkaran Bibit Lada Natar 1 Prima Tani Lampung Utara - Suprapto Suprapto; Rr. Ernawati (Politeknik Negeri Lampung., 2010)
The study analysis income nursery pepper Natar 1 hase been done in Prima Tani North Lampung. The studied hope to know farmer income were inproved nursery pepper cutting and successfully pepper seedling. The studied used 14.000 pepper cutting one leaf, every pepper cutting planted on soil and dung cow mixture (1:1) in polibag volume 1,0 kg and than pepper cutting were planted in polibag to covered by tranparan plastic as long as 35 days. After 35 days plastic covered to open, and the pepper seedling to manage up to 5-6 month. The result studied shown that nursery pepper cutting died about 21%, pepper seedling to be able to planted in 6 month age about 69% and not yet to be able to planted about 10%. Nursery pepper management have income 52,85% about Rp 1.585,50 per seedling when price pepper seedling Rp 3.000,- per plant. On nursery pepper production, farmer must be have pepper garden or mini pepper garden were intensive cared as soure of better pepper cutting, decided variety and no pest and desease. Nursery pepper management 14.000 pepper cutting have total cost Rp 19.803.000, farmer to be able to producing 9.660 pepper seedling and the price about Rp 28.980.000 and farmer income about Rp 9.177.000,- with B/C ratio 1,46 as long as 6 month and 1400 leafover pepper seedling already planting after 6 month. Keywords : Nursery , pepper, seedling ; income